KEDUDUKAN DAN KEKUATAN HUKUM KEPUTUSAN BERSAMA MENTERI DALAM PERSPEKTIF PERATURAN PERUNDANG- UNDANGAN DI INDONESIA - Laili Ramadhani Setiawatidina; Mexsasai Indra; Zulwisman Zulwisman (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2022)
Joint Ministerial Decree is a decision made by more than one minister on amatter which each minister concerned has an interest in regulating. Decree withthe minister is not regulated in Indonesian laws and regulations. Theimplementation of the position and legal force of the Joint Ministerial Decree isstill a matter of debate in terms of several aspects, such as the definition, content ofthe Joint Ministerial Decree. One example of a controversial SKB is SKB No.2/KB/2021 Concerning the Use of Uniforms and Attributes for Students, Educators,and Education Personnel in Schools Organized by Local Governments atElementary and Secondary Education Levels and Number KEP-033/A/JA/6/2008Concerning Warnings and Orders to Adherent Members, and/or Members of theManagement of the Indonesian Ahmadiyya Congregation (JAI) and members of thepublic.The purposes of this study are: First, to find out how the position and legalpower of joint ministerial decisions in the perspective of legislation in Indonesia,Second, to find out the ideal concept of the position and legal power of jointministerial decisions in the perspective of laws and regulations in Indonesia.The author conducted this research using a normative research method orliterature study which discusses the vertical and horizontal synchronization of lawrelating to the Joint Ministerial Decree in the perspective of legislation inIndonesia. In addition to issuing regulations, the minister also has the authority toissue policies in the form of decisions. Second, the ideal concept of this Ministerialdecree is a change to law No. 12 of 2011 and the president issues a regulation(presidential regulation) that confirms the position, substance, and procedure of ajoint ministerial decree.Keywords: Joint Decree, Minister, Legislation.